On the Use of a Complex Indicator of the Stability of Permutation Entropy of Time Series Fragments When Analyzing Infrasound Monitoring Signals of the Altai Republic - Kudryavtsev Nikolay; Frolov Ivan; Safonova Varvara (Russian Journal of Earth Sciences)
This paper discusses one of the approaches that allows us to assess the degree of complexity or randomness of fragments of a time series in order to detect infrasound or geomagnetic signals in the results of observations of the dynamics of the natural or man-made processes under study. In our case, we are talking about monitoring the infrasound background on the territory of the Altai Republic. To solve the problem of estimating the required characteristics of a time series with minimal computational costs and in real time, a complex indicator of the stability of permutation entropy is introduced, since estimating the value of classical permutation entropy for n = 3 (the most commonly used version of permutation entropy) does not allow solving the problem with sufficient accuracy.